Induced sterility in fish and its potential and challenges for aquaculture and germ cell transplantation technology: A review - Golpour, Amin; Siddique, Mohammad Abdul Momin; Siqueira-Silva, Diógenes Henrique [UNESP]; Pšenička, Martin (Springer Nature, 2016)
Interest in reproductively sterile fish in aquaculture has prompted research into their production. Several methods are available for inducing sterility and optimizing its application in the global fishery industry. Sterilization can potentially be accomplished through irradiation, surgery, or chemical and hormonal treatment. Alternative approaches include triploidization, hybridization, and generation of new lines via advanced biotechnological techniques. Triploids of many commercially important species have been studied extensively and have been produced on a large scale for many years. Novel approaches, including disruption of gonadotropin releasing hormone signalling and genetic ablation of germ cells, have been developed that are effective in producing infertile fish but have the disadvantage of not being 100% reliable or are impractical for large-scale aquaculture. We review currently used technologies and recent advances in induction of sterility in fish, especially those intended for use in germ cell transplantation. Knowledge of the implications of these approaches remains incomplete, imposing considerable limitations.
Keywords: biotechnological tools; germ cell; reproductive containment; sterility